2007
DOI: 10.1007/s00520-007-0352-6
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous morphine consumption in outpatients with cancer during their last week of life—an analysis based on patient-controlled analgesia data

Abstract: During their end-of-life phase, cancer patients on i.v. morphine PCA showed a stable daily opioid need.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…11.5.1, SPSS Inc opioid need which increases in the children's last days of life [6,10,22,23,29,31]. In adults, studies analysing opioid doses administered in the patients' last week of life showed only slight increases in the MED [12,13,28,34].…”
Section: Discussionmentioning
confidence: 95%
“…11.5.1, SPSS Inc opioid need which increases in the children's last days of life [6,10,22,23,29,31]. In adults, studies analysing opioid doses administered in the patients' last week of life showed only slight increases in the MED [12,13,28,34].…”
Section: Discussionmentioning
confidence: 95%
“…The use of outpatient opioid PCA to treat cancer pain has been described in several adult studies, [8, 1012] in a review article of adult studies, [9] and in one study of combined adult and pediatric patients. [13] Even though the use of PCA in pediatric and young adult patients has not previously been specifically investigated in the outpatient setting, its safety in pediatric inpatients has been established. [2, 4, 7]…”
Section: Discussionmentioning
confidence: 99%
“…While extensive literature describes the use of PCA in the inpatient setting, little has been published describing its use for chronic pain management in the outpatient setting in adults, [812] and even fewer studies have included children in the study group [13] or examined the use of PCA in the outpatient setting for pain control in dying children. [1]…”
Section: Introductionmentioning
confidence: 99%
“…11 In a recent retrospective analysis of intravenous morphine patient-controlled analgesia in home care patients, opioid doses remained stable, in the range of 96 to 115 mg/d, in the last week of life, although the use of such a technique is questionable in severely ill patients. 12 In a hospice setting in United Kingdom, lower doses of opioids were used in the last week of life. The mean daily opioid dose increased from 42 to 55.5 mg over the last 7 days of life, with an increase in the number of patients receiving opioids from 61% at admission up to 89%.…”
Section: Discussionmentioning
confidence: 99%
“…Only 7% to 12% of patients required doses of more than 300 mg of morphine. [2][3][4][5][6][7][8][9][10][11][12][13] Unfounded concerns about the possible life-shortening effect of opioids may result in less than optimal symptom management in end-of-life care. 14 Some studies have examined the relationship between the use of opioid and survival but none of them reported that opioids had shortened life.…”
Section: Discussionmentioning
confidence: 99%